Feminine memory in Jabra Ibrahim Jabra s narratives - Al-Bayati, Sawsan H. J. (Humanities Journal of University of Zakho, 2014)
Our narrative comparison is based on the dual memory. The female in a narrative text derives her dominance from the prominent feminine voice, away from the in fluence and interference of the man, which beside the fact that it cannot be separated from it is in fact strongly related to it. It poses the problem of the man dominating his effectiveness in absentia physically effectively in the preones of memory, in the sense that it is a voice based on the effectiveness of absence – presence not presence – absence. The text here, depends on the feministic feminine memory, and the man moves through this memory because narrative dominance is feminine and tyrant in its voice and present in the presence of masculinity. The feminine memory refers to the works of Jabra Ibrahim Jabra, his novels, which focus on the narrative I or the abundant presence of the speaker pronoun. This presence does not come arbitrarily there are ideas and visions that Jabra presents through this pronoun. To ensure this study meets its objectives, we decided to delve into the events of only one novel entitled diaries of affan mirage because we found it to be more biased and philosophical to this narrative perspective, in other words.1- we found that this I functions in a broad textual space scope in this novel and therefore, is it the most compelling account of it.2- it functions distinctly from a female perspective which is one of the main reasons that led us to making this comparison there is a clear narrative fiction of the I reflected in the text in that the whole text is the diary of a woman, taking into account the preoence of the man, which is a mental presence in the memory of the woman, this memory attracts the man and treats him in a way that is different from the way she treats her female counterpart, or the way she treats another woman.